La sintomatología ansiosa y el bajo rendimiento académico en los estudiantes del octavo grado de la Escuela de Educación Básica IV Centenario de la ciudad de Loja, periodo lectivo, 2022-2023. - Cortés Díaz, Katherine Del Pilar (2023)
The anxious symptomatology currently represents an increasingly common issue, due to the changing pace of life and the various challenges that citizens must face. This reality is not unfamiliar to adolescents within the school context. For this reason, the objective of the current study is proposed as follows: To determine the relationship between anxious symptomatology and low academic performance among eighth-grade students at the “Escuela de Educación Básica IV Centenario” in the city of Loja, Ecuador. The collected results reveal a clear connection between these two factors, highlighting that the presence of anxious symptomatology directly affects students with low performance. However, in certain cases, the low academic performance may stem from other types of factors. The research also demonstrates that females are more susceptible to experiencing high levels of anxious symptomatology than males. Therefore, it is advisable to intervene by implementing a prevention plan to address anxiety symptoms, aiming to enhance academic performance, as well as the well-being and emotional health of students. To ensure a quality of life that corresponds to their needs, considering that eighth-grade students are undergoing the crucial stage of adolescence, which plays a pivotal role in their subsequent development, providing them with tools to secure their well-being through psychology as the science of knowledge is paramount. This is in service to society, especially the student population. Keywords: Anxious symptomatology, prevention plan, emotional health, academic performance.